A study on fish market and marketing system in Gazipur district, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Marketing of fish and fishery products in the three markets of Gazipur district were studied during the period from November 2014 to April 2015. Data were collected from three different markets. A total of 45 traders (retailers), 15 from each market were interviewed at the market center. A survey questionnaire was developed, pre-tested and finally used for collection of data. Data were collected from the three different fish markets through questionnaire interviews and focus group discussions. Three types of marketing channel were found to be operated in the selected markets. The market chain from fishermen to consumer passes through a number of intermediaries: local traders, agents/suppliers, retailers and consumers. The shorter marketing chain which included the fish farmers, retailers and consumers was found to be more beneficial to the fish producers. There are some fish species available in three different markets, such as Indian major carps i.e. rui, catla, mrigal and Exotic fish i.e. silver carp, grass and common carp, tilapia, pangas etc. The price of fish depended on size, weight, season, availability, species quality and size of fishes. Different types of dried and salted fish were available in the markets. A number of constraints for fish marketing were reported by the retailers, the constraints were lack of storage facilities, poor supply of ice, exploitation by middlemen, lack of money and lack of infrastructure.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 7-13